LINGUOCOGNITIVE AND PRAGMALINGUISTIC BASIS OF THE IMPLICITY CATEGORY (Scientific journal of the Fergana State University, 2023)
This article examines the phenomenon of implication, which is an important terminological unit of pragmalinguistics, one of the new areas of linguistics. Also, in the methodological and functional study of the phenomenon of implication, scientists note the existence of approaches based on different points of view and diversity in the principles of classification. The theoretical foundations and research methods are presented in detail. As a general theoretical method, the work uses methods of comparison, contrast, semantic and pragmatic analysis, and generalization. The phenomenon of implication is reduced to analysis because of its implicit judgment. The phenomenon of implication is clarified through derived linguistic data.